Interrelation between Physical Activity and Anxiety in the Covid-19 Pandemic Era - Gerhana Sukma Hendra; Zayadi Zainuddin; Riry Ambarsarie (Jurnal Ilmu Kedokteran, 2022)
The Covid-19 pandemic is a global health problem that is affecting the entire population of the world. Decreased social interaction and lack of social support, also the demands to get good grades have a negative impact on student's mental health levels, one of the mental health problems is anxiety. The purpose of this study was to determine the relationship between the levels of physical activity and anxiety during the distance learning process in the Covid-19 pandemic era. This study used an observational analytical study with a cross-sectional design. The respondents were 107 Bengkulu University college students, consecutive sampling technique. Assessment using the Global Physical Activity Questionnaire and the Hamilton Anxiety Rating Scale questionnaire. The relationship between variable was analyzed by the Gamma correlation test. The results showed that the most level of physical activity in the research subjects was in the low category (59,8%), with the most anxiety level being mild anxiety (47,7%). Based on statistical analysis obtained p = 0,000 and r = -0,499. This study shows that there is a significant relationship between the levels of physical activity and anxiety in Bengkulu University students during the distance learning process in the Covid-19 pandemic era with a moderate correlation.